Differential effect of hydroxyapatite nano-particle versus nano-rod decorated titanium micro-surface on osseointegration. (August 2018) - Bai, Long; Liu, Yanlian; Du, Zhibin; Weng, Zeming; Yao, Wei; Zhang, Xiangyu; Huang, Xiaobo; Yao, Xiaohong; Crawford, Ross; Hang, Ruiqiang; Huang, Di; Tang, Bin; et al.
Graphical abstract: Abstract: Coating materials applied for intraosseous implants must be optimized to stimulate osseointegration. Osseointegration is a temporal and spatial physiological process that not only requires interactions between osteogenesis and angiogenesis but also necessitates a favorable immune microenvironment. It is now well-documented that hierarchical nano-micro surface structures promote the long-term stability of implants, the interactions between nano-micro structure and the immune response are largely unknown. Here, we report the effects of microporous titanium (Ti) surfaces coated with nano-hydroxyapatite (HA) produced by micro-arc oxidation and steam-hydrothermal treatment (SHT) on multiple cell behavior and osseointegration. By altering the processing time of SHT it was possible to shift HA structures from nano-particles to nano-rods on the microporous Ti surfaces. Ti surfaces coated with HA nano-particles were found to modulate the inflammatory response resulting in an osteoimmune microenvironment more favorable for osteo-/angio-genesis, most likely via the activation of certain key signaling pathways (TGF-β, OPG/RANKL, and VEGF). By contrast, Ti surfaces coated with nano-rod shaped HA particles had a negative impact on osteo-/angio-genesis and osteoimmunomodulation. In vivo results further demonstrated that Ti implant surfaces decorated with HA nano-particles can stimulate new bone formation and osseointegration with enhanced interaction between osteocytes and implant surfaces. This study demonstrated that Ti implants with micro-surfaces coated with nano-particle shaped HA have a positive impact on osseointegration. Statement of Significance: Osteo-/angio-genesis are of importance during osteointegration of the implants. Recent advances unravel that immune response of macrophages and its manipulated osteoimmunomodulation also exerts a pivotal role to determine the fate of the implant. Surface nano-micro modification has evidenced to be efficient to influence osteogenesis, however, little is known links nano-microstructured surface to immune response, as well the osteoimmunomodulation. This study demonstrates that the nano-particles decorated micro-surface, compared with the nano-rods decorated micro-surface enables osteogenesis and angiogenesis concurrently that has not been investigated previously. This study also unravels that the immune response of macrophages can be manipulated by the nano-micro surface, especially the nano-dimension matters, leading to a differential effect on osteointegration. The additional knowledge obtained from this study may provide foundation and reference for future design of the coating materials for implantable materials.